Meneropong Semangat Hidup Gen Z dalam Menjalankan Hubungan Tanpa Status - Naja, Ahmad Wildan Idrokun; Suryani , Destiani Ayuk; Sijabat, Rauly (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The phenomenon of relationship without status (situationship) has become increasingly common among Generation Z along with the rapid development of digital technology and shifts in social values regarding romantic commitment. This type of relationship is characterized by emotional closeness similar to dating, yet without clear formal status. This study aims to explore Generation Z’s perspectives on situationships, identify the motivations behind engaging in such relationships, and analyze the forms of life spirit maintained amid relational uncertainty. This research employs a qualitative approach using in-depth interviews with five students from Universitas PGRI Semarang who have experienced or are currently involved in a situationship. Data analysis was conducted using the interactive model proposed by Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Generation Z perceives situationships as flexible and non-binding relationships, although they may lead to emotional uncertainty. The main motivations include the desire for freedom, focus on self-development, and the influence of digital culture. Despite relational ambiguity, Generation Z demonstrates a strong life spirit through resilience, effective emotional regulation, and a clear orientation toward long-term life goals.